Participant Motivation of Physical Activity in Leisure Time for Women: 女性休間身體活動參與動機之探討 - WANG, Hsiu Hua (Asian Journal of Physical Education & Recreation, 2003)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purpose of this paper was to explore the participant motivation of physical activity in leisure time for women. From the review of literatures on physical activity for women, it was ascertained that increased physical activity was highly associated with improved physical health and mental health. However, some researchers concluded some facts about women's participation in physical activity; (1) most adult women either don't do the recommended amount of physical activity or are completely inactive; (2) women are more inactive than men. Furthermore, recognizing and referring to the female participants' motivation of physical activity in leisure time, physical activity intervention programs would be designed more effectively and implemented more successfully. 本文主要的目的是探討女性於閒暇時參與身體活動之動機。從相關文獻研究指出其主要身體活動參與動機因素如下：(1)人與人之間的轉向和調節 (2)個人能力 (3)逃離日常生活規範 (4)人與人之間正向發展 (5)轉移注意力 (6)人與人之間能力 (7)尋找異性朋友 (8)追求快樂感 (9)追求刺激 (10)追求冒險 (11)健康及幸福安寧感 (12)入迷 (13)社會互動 (14)創造力 (15)自我實現。